The Palgrave Handbook of Family Policy - Nieuwenhuis, Rense; Van Lancker, Wim (Springer Nature, 2020)
This open access handbook provides a multilevel view on family policies, combining insights on family policy outcomes at different levels of policymaking: supra-national organizations, national states, sub-national or regional levels, and finally smaller organizations and employers. At each of these levels, a multidisciplinary group of expert scholars assess policies and their implementation, such as child income support, childcare services, parental leave, and leave to provide care to frail and elderly family members. The chapters evaluate their impact in improving children's development and equal opportunities, promoting gender equality, regulating fertility, productivity and economic inequality, and take an intersectional perspective related to gender, class, and family diversity. The editors conclude by presenting a new research agenda based on five major challenges pertaining to the levels of policy implementation (in particular globalization and decentralization), austerity and marketization, inequality, changing family relations, and welfare states adapting to women's empowered roles.